If h(x) = 3x − 1 and j(x) = −2x, solve h[j(2)] and select the correct answer below.

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

If h(x) = 3x − 1 and j(x) = −2x, solve h[j(2)] and select the correct answer below.

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

−11 11 −13 13
hmm, what's J(2) anyway?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

j(2)=j(x) x=2. @jdoe0001
well,, j(x) = -2x so if x = 2 that means j(2), then j(2) = ?
-4
yeap so now we know that j(2) = -4 thus \(\bf h({\color{brown}{ j(2)}}\iff h({\color{brown}{ -4}}=-3({\color{brown}{ -4}})-1\)
okay so -4=11
hmm \(\bf h({\color{brown}{ j(2)}})\iff h({\color{brown}{ -4}})=-3({\color{brown}{ -4}})-1 \\ \quad \\ h(j(2))=-12-1\implies h(j(2))=-13\)
so c, -13? Thanks for the help. Can you help with one more?
hmm actually have a typo, is 13 no -13 but anyhow \(\bf h({\color{brown}{ j(2)}})\iff h({\color{brown}{ -4}})=3({\color{brown}{ -4}})-1 \\ \quad \\ h(j(2))=-12-1\implies h(j(2))=-13\)
sure, post anew, thus more eyes
so 13
not -13
3* -4 = -12 -12 - 1 = -13
so the answer is -13?
well... the answer is \(\bf h({\color{brown}{ j(2)}})\iff h({\color{brown}{ -4}})=3({\color{brown}{ -4}})-1 \\ \quad \\ h(j(2))=-12-1\implies h(j(2))=-13\) :)
but its multiple choice, so h(j(2))=-13
thanks!
yw

Not the answer you are looking for?

Search for more explanations.

Ask your own question